Report of the Working Party on Homebirths and Alternative Birth Centres : the National Health and Medical Research Council 104th session. - National Health and Medical Research Council (Australia). Working Party on Homebirths and Alternative Birth Centres; National Health and Medical Research Council (Australia) ([Canberra] : National Health and Medical Research Council, 1987)
Terms of reference: (a) to carry out an overview of the homebirth movement with the aim of establishing better professional relationships between homebirth practitioners and the medical profession, and of establishing better relationships between families and support people and the medical profession; (b) to develop principles for alternative birth practice, in and out of hospital; (c) to look at criteria for education of homebirth midwives; (d) report to the Women's Health Committee.
3. Overview of homebirth in Australia -- 4. Relationships between providers and consumers -- 6. Principles of safe homebirth -- 7. Training of homebirth midwives.
Cover title.
Bibliography: Appendix 5.
Keywords: Natural childbirth -- Australia; Childbirth at home -- Australia; Midwives -- Australia; Home childbirth -- Australia; Natural childbirth -- Australia; Nurse midwives -- Australia; Childbirth -- Statistics